Hypoxic Ischemic Encephalopathy in Neonates with Birth Asphyxia - A Hospital Based Study - Adhikari, Jyoti; Paudel, Deepak (Journal of Nepalgunj Medical College, 2021)
Introduction: Each year approximately 4 million babies are born asphyxiated, which results in 1 million deaths and an equal number of serious neurological sequelae. One of the commonest organs involved in birth asphyxia is brain which may lead to a syndrome of clinical manifestation called Hypoxic Ischemic Encephalopathy (HIE). Aims: To find out possible maternal and neonatal risk factors for Hypoxic Ischemic Encephalopathy, to analyze clinical presentations and outcome of HIE in asphyxiated newborns. Methods: Hospital based observational study was carried out among fifty newborns with Apgar score less than 7 at 1 minute of life admitted in Nepalgunj Medical College Teaching Hospital, Kohalpur, Banke. Results: The incidence of birth asphyxia and birth asphyxia with HIE were 37.2 per 1000 live births and 14 per 1000 live births with male: female ratio of 1.27:1. Most of the neonates 22(44%) were in HIE stage II. Meconium stained amniotic fluid 18 (36%) was the most common intrapartum risk factor followed by maternal use of intrapartum medications 14 (28%), Premature Rupture of Membrane (PROM) 8 (16%), prolonged labor 5 (10%) and obstructed labor 6 (12%). Four (8%) asphyxiated neonates with HIE had cord prolapse and 7 (14%) had cord around the neck. The most common resuscitation done was bag and mask ventilation (56%) (P<0.05). Majority of the studied neonates were of normal birth weight (76%) and head circumference (84%) (P<0.05) with clinical presentations of respiratory distress (88%), seizures (44%), apnea (22%), bradycardia (8%), tachycardia (6%) and bulged anterior fontanel (6%). The overall mortality of neonates with HIE was 20% of which most were of HIE stage III. Conclusion: Certain measures could be taken to prevent birth asphyxia: early detection and intervention of high risk pregnancy, prompt and effective resuscitation of asphyxiates newborns.